Preparation of a Feasibility Study for The Development of Balobaloang Lompo Port, Pangkajene Islands Regency, South Sulawesi Province - Zainul Aris Hasibuan; Dyah Ersita Yustanti (Journal Research of Social Science, Economics, and Management, 2023)
This study aims to prepare a feasibility study for the development of Balobaloang Lompo Port in Pangkajene Islands Regency, South Sulawesi Province. The objective is to evaluate the potential and consider important factors in port development, including economic, social, environmental, and technical analyses. The research methodology involves field surveys, primary and secondary data collection, as well as quantitative and qualitative analysis. The gathered data will be used to identify development needs and opportunities for the port, as well as assess their impact on various related aspects. The findings of this study will provide a comprehensive understanding of the feasibility of developing Balobaloang Lompo Port. The study will consider various factors, such as environmental sustainability, economic contributions, social benefits, and existing infrastructure readiness. The feasibility study is expected to serve as a guide for the government, financial institutions, and other stakeholders in making decisions regarding the development of Balobaloang Lompo Port. With comprehensive information and careful analysis, it is anticipated that the port development can be carried out effectively and sustainably, while maximizing benefits for the local community and the surrounding region.